3D Flexible Frequency Selective Surface with Stable Electromagnetic Transmission Properties. Issue 7 (5th January 2022) - Fan, Xuanqing; Pan, Zijian; Chen, Sihong; Li, Yuhang; Zhao, Zhao; Pan, Taisong
Abstract: Frequency selective surfaces (FSS) that can be tightly laminated to complex nondevelopable surfaces have a wide range of applications in many engineering areas. This paper presents a 3D flexible FSS prepared by mechanically guided 3D assembly, capable of being conformally adhered to complex surfaces, while maintaining stable frequency selective properties as well as transmission performance. The stretching strain applied to the prestrained ecoflex substrate can precisely tune and control the buckled 3D metal structures, which leads to the stretchability of the flexible FSS, introduces the increase of the inductance inside the metal cells, and expands the metal gap resulting in a reduction of the capacitance between the unit cells. The mutual correlation of capacitance and inductance ensures in the mechanism that the FSS transmission characteristics will not be significantly affected by the applied strain, as verified by calculations using the equivalent circuit method. Both the results obtained by the experiments and simulations indicate that the resonant frequency of the 3D flexible FSS is 5.7 GHz and the bandwidth at −10 dB is 0.94 GHz, while the resonant frequency shift will not exceed 0.45 Hz, and −10 dB bandwidth change will not exceed 0.32 GHz with applied strain of 17.8% in the ecoflex substrate. At the same time, the 3D flexible FSS maintains stable transmission performance for oblique incidence, with only 0.5 GHz frequency shift at 45° incidence. This stretchable flexible FSS with stable electromagnetic (EM) properties may find potential applications in EM shielding and spatial filtering due to its high flexibility, ready applicability, and cost‐effectiveness. Abstract : This paper presents a 3D flexible frequency selective surface prepared by mechanically guided 3D assembly, capable of being conformally adhered to complex surfaces, which can maintain stable frequency‐selective properties as well as transmission performance when subjected to biaxial stretching strains.